Oscillating lithium ion-acceptor fluorine-donor electrolytes for practical fast-charging high-energy lithium metal pouch cells - Ruan, Digen; Wang, Yanru; Guo, Jiasen; Cui, Zhuangzhuang; Nian, Qingshun; Ma, Zhihao; Wang, Dazhuang; Fan, Jiajia; Ma, Jun; Xiong, Bingqing; Dong, Qi; Cao, Ruiguo; et al. (Energy & environmental science, 2025)
High-voltage Li metal batteries (LMBs) are promising high-energy-density energy storage solutions. However, achieving fast-charging under practical conditions has been a formidable challenge. Here, we synthesized 2-fluoro-1,1-dimethoxy-ethane (FDMN) with a super-lithiophilic fluorine group as a strategical co-solvent to address the long-standing dilemma between rapid Li + transport in bulk electrolytes and stable electrode-electrolyte interphases. As a Li + acceptor, FDMN shows a unique oscillating feature to enable fast Li + exchange across solvation complexes due to the asymmetric polar fluorine site, achieving a high Li + transference number of 0.80. As a fluorine donor, the strong fluorine-donating ability of FDMN facilitates the formation of an amorphous inorganic SEI interlaced with nanocrystalline Li 2 O on the Li metal anode and a LiF-rich CEI on the high-voltage cathode. FDMN-based electrolytes improve Li coulombic efficiency under high current densities and enable excellent 1C/2C fast-cycling for 4.5 V nickel-rich LMBs with inhibited Li dendrite growth and Li consumption. Significantly, for the first time, a practical 2 A h NMC811|Li pouch cell (412 W h kg −1 energy density based on the total mass) with a lean electrolyte (1.5 g A h −1 ) achieves over 120 stable cycles under 1C fast-charging and 2C fast-discharging. This electrolyte design principle presents an encouraging approach for realizing practical fast-charging high-energy-density LMBs. An oscillating Li + -acceptor fluorine-donor electrolyte incorporating a new co-solvent with an asymmetric super-lithiophilic fluorine group resolves the dilemma between fast electrolyte Li + transport and stable interphases.